Rwanda : First Review of the Standby Credit Facility Arrangement and Sixth Review Under the Policy Support Instrument, Request for Waiver and Modification of Performance and Assessment Criteria-Press Release; and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Rwanda's First Review of the Standby Credit Facility (SCF) Arrangement and Sixth Review Under the Policy Support Instrument (PSI), Request for Waiver and Modification of Performance and Assessment Criteria. Performance under the PSI and SCF-supported programs remains on track. Nearly all quantitative program targets and structural benchmarks were respected: two quantitative targets were missed by minor amounts, and one benchmark was delayed. The IMF staff recommends approval of the first review of the SCF arrangement and the sixth review of the program supported by the PCI, as well as the request for waiver of nonobservance of the continuous external arrears criterion, and modification of forthcoming program criteria.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet